Bullous Drug Reaction with Dipeptidyl Peptidase-4 (DPP-4) Inhibitors. Issue 1 (March 2022) - Geetha, K.; Puja,
Hypoglycemic drugs in the dipeptidyl peptidase-4 (DPP-4) inhibitor class are used as a second-line treatment for type 2 diabetes mellitus. With DPP-4 inhibitors, there have been a few reports of cutaneous side effects such as bullous response, fixed drug eruption, and photosensitivity. There is no definitive pathophysiology for the above mentioned allergic reactions. Sitagliptin phosphate belongs to the DPP-4 inhibitor class. This is a case report of a sitagliptin-induced bullous drug reaction manifesting three weeks after starting therapy. He had bullous pemphigoid-like eruptions all over the body. The patient showed improvement once sitagliptin was discontinued alon with oral and topical steroid treatment.